1991
DOI: 10.1002/bjs.1800780629
|View full text |Cite
|
Sign up to set email alerts
|

Combined portal vein and liver resection for carcinoma of the biliary tract

Abstract: Twenty-nine patients with advanced carcinoma of the bile duct or gallbladder underwent combined portal vein and liver resection. Segmental excision of the portal vein was performed in 16 cases and wedge resection of the vessel wall in 13. The operative mortality rate was 17 per cent. The median survival for the 24 patients who left hospital was 19.8 months. Actuarial survival rates at 1, 3 and 5 years for all 29 patients were 48 per cent, 29 per cent, and 6 per cent respectively, whereas the median survival fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
147
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(147 citation statements)
references
References 20 publications
0
147
0
Order By: Relevance
“…Much controversy exists about the optimum surgical procedure for gallbladder cancer. Recommendations have ranged from simple cholecystectomy to ultraaggressive resections consisting of combined major liver resection and pancreaticoduodenectomy (Nimura et al, 1991). The major problem is that operations required for complete resection of cancer are associated with high morbidity and mortality (Ouchi et al, 1987;Ogura et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Much controversy exists about the optimum surgical procedure for gallbladder cancer. Recommendations have ranged from simple cholecystectomy to ultraaggressive resections consisting of combined major liver resection and pancreaticoduodenectomy (Nimura et al, 1991). The major problem is that operations required for complete resection of cancer are associated with high morbidity and mortality (Ouchi et al, 1987;Ogura et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Of the 21 cases treated with palliative operation, the post-surgery mortality was 14% and the mean survival range was only 7 mo. Nimura [30,31] performed a liver and bile duct resection combined with Whipple's operation in five patients with hilar tumors. Two of the five patients died after surgery and the three survivors died 8, 10 and 27 mo later.…”
Section: Discussionmentioning
confidence: 99%
“…If the tumor shows the signs of invasion of the perivascular connective tissue, en bloc resection of the right hepatic artery is advocated to obtain a negative surgical margin; therefore, right hemihepatectomy is recommended. If tumor invasion of the portal vein is suspected based on the preoperative imaging or the intraoperative findings, combined resection of the portal vein and reconstruction are the treatment of choice to obtain a negative radical margin [39][40][41] .…”
Section: Vertical Invasion Of the Bile Ductmentioning
confidence: 99%
“…Previously, invasion of a major vessel meant an unresectable tumor. Recent reports have shown improved results when portal vein resection and reconstruction are performed together with major hepatectomy [39][40][41]89] . Neuhaus et al [66] reported a 5-year survival rate of 65% after curative resection of hilar bile duct cancer with portal vein resection and reconstruction.…”
Section: Combined Vascular Resection and Reconstructionmentioning
confidence: 99%